Teacher-Student Interaction: A Strong Foundation for Quality Character Education - Sari, Dewi Purnama; Sutarto, Sutarto (Ta'dib, 2024)
Character education is critical in developing students’ attitudes and personalities. One approach that can be used is through teacher interaction with students. This study aims to reveal teachers’ approach to interacting with students to develop good character values. This study is a qualitative study with a phenomenological approach. The research informants were eight teachers who intensively interacted with students for over a year. The data collection technique used in-depth interviews. The data analysis technique used was interpretative phenomenological analysis (AFI), which includes three stages: horizontalization, developing meaning units, and presenting the phenomenon’s essence. To obtain valid data, researchers conducted source triangulation. The study results showed that intensive teacher-student interaction, both classically and individually, can provide understanding and foster students’ awareness of having good character. Therefore, to build students’ character in a better direction, teachers are strongly advised to constantly interact with students intensively, both classically and individually, to foster sensitivity and students’ means of having good character.